2013
DOI: 10.3390/ijerph10010417
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Urban Green Space as a Health Resource: A Qualitative Comparison of Visit Motivation and Derived Effects among Park Users in Sheffield, UK

Abstract: With increasing interest in the use of urban green space to promote human health, there is a need to understand the extent to which park users conceptualize these places as a resource for health and well-being. This study sought to examine park users’ own reasons for and benefits from green space usage and compare these with concepts and constructs in existing person-environment-health theories and models of health. Conducted in 13 public green spaces in Sheffield, UK, we undertook a qualitative content analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
191
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(215 citation statements)
references
References 104 publications
15
191
0
9
Order By: Relevance
“…Similar results are obtained even after only about 15 to 20 minutes of walking in the forest [8][9][10][11][12]. This highlights the importance of green spaces in the city [14] and garden walking [15]. However, the specific effects of the forest are not necessarily clear.…”
Section: Discussionsupporting
confidence: 72%
“…Similar results are obtained even after only about 15 to 20 minutes of walking in the forest [8][9][10][11][12]. This highlights the importance of green spaces in the city [14] and garden walking [15]. However, the specific effects of the forest are not necessarily clear.…”
Section: Discussionsupporting
confidence: 72%
“…On the one hand, the wellbeing outcomes of parks might directly motivate people to use them (Kaplan and Kaplan 1989;Home et al 2012). Indeed, experiencing nature is a commonly stated reason for people to visit public green space (Chiesura 2004;Irvine et al 2010Irvine et al , 2013. However, while people often express a desire to interact with nature, field observations in Sheffield, UK, revealed that once inside parks visitors tended to prefer locations with lower tree cover (Irvine et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also shown that living near green space has a positive influence on mental health [4,5] and happiness [6][7][8]. Studies conducted by Beyer et al [5] show that by living in a neighborhood with more green space is associated with better mental health levels than living in neighborhoods with less green space.…”
Section: Introductionmentioning
confidence: 99%